Tex. Act of April 12, 1871, Art. 320 - (:unkn) unknown (General Publisher, 1871)
Expands the places where carrying a weapon may be prohibited to include "places where persons are assembled for amusement [... including] any circus, show, or public exhibition of any kind [...]" - however, the law makes an exception "as may be required or permitted by law." Gun shows are permitted by law under CA Penal Code § 27300 et seq. The restrictions on general public carry may be overbroad and thus invalid in light of the Bruen decision.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES